WALL SHEAR STRESS IN A SUBJECT SPECIFIC HUMAN AORTA — INFLUENCE OF FLUID-STRUCTURE INTERACTION - LANTZ, JONAS; RENNER, JOHAN; KARLSSON, MATTS (International journal of applied mechanics, 2011)
Vascular wall shear stress (WSS) has been correlated to the development of atherosclerosis in arteries. As WSS depends on the blood flow dynamics, it is sensitive to pulsatile effects and local changes in geometry. The aim of this study is therefore to investigate if the effect of wall motion changes the WSS or if a rigid wall assumption is sufficient. Magnetic resonance imaging (MRI) was used to acquire subject specific geometry and flow rates in a human aorta, which were used as inputs in numerical models. Both rigid wall models and fluid-structure interaction (FSI) models were considered, and used to calculate the WSS on the aortic wall. A physiological range of different wall stiffnesses in the FSI simulations was used in order to investigate its effect on the flow dynamics. MRI measurements of velocity in the descending aorta were used as validation of the numerical models, and good agreement was achieved. It was found that the influence of wall motion was low on time-averaged WSS and oscillating shear index, but when regarding instantaneous WSS values the effect from the wall motion was clearly visible. Therefore, if instantaneous WSS is to be investigated, a FSI simulation should be considered.